Morphological variations of Eimeria spp., in beef cattle in Bangkalan District, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hastutiek P, Lastuti NDR, Suwanti LT, Kurniawati DA, Efendi MH. 2022. Morphological variations of Eimeria spp., in beef cattle in Bangkalan District, East Java, Indonesia. Biodiversitas 23: 3457-3461. Eimeria spp. infection in cattle can cause high economic losses and increase the susceptibility to infection with other infectious diseases, so the government needs attention to coccidiosis in cattle. Coccidiosis can easily be found in farms that are managed with poor management systems, housing sanitation, and poor environment. Cases of coccidiosis often do not show clinical symptoms and cause sudden death of livestock. This study aimed to identify Eimeria spp., morphologically the cause of coccidiosis in beef cattle. Fresh feces were collected from 120 beef cattle from smallholder farms in Bangkalan District. The results of stool examination revealed that 70 (58.33%) positive samples containing Eimeria spp. oocysts. The six Eimeria species obtained from the samples were: Eimeria bovis, Eimeria zuernii, Eimeria ellipsoidal, Eimeria subspherica, Eimeria aubernensis, and Eimeria canadinensis. Calculation of oocysts per gram (OPG) of feces showed that most cows were infected with mild to moderate coccidiosis. Morphological identification can be used to diagnose Eimeria species in coccidiosis in beef cattle.
Keywords: Beef cattle, coccidiosis, Eimeria spp., infectious diseases, morphological variations, OPG